Institutions of Georgia for governance on national minorities: an overview - Sordia, Giorgi (2009)
Abstract: 'This paper aims to discuss the institutional set-up around civil integration and minority protection issues in Georgia since the 'Rose Revolution', and the study reviews the state structures relevant for governance and legislative practices on civil integration and minority issues. It seeks to provide an overview of the institutional problems that beset civic integration by presenting a brief outline of the history and responsibilities of the relevant state bodies and analyzing some of the problems in the current institutional arrangements. The research for this paper has been conducted by way of consultations and interviews with the representatives of the bodies concerned, both executive and legislative. Use is also made of official documents, principally the mandates, constituting decrees, legal documents and regulations of the bodies covered by our research. The paper is divided into three sections. The first section examines the emergence of institutional structures for handli